The Bukhorians We Don't Know or Sabbaq Bukhari - Literary Scholar (Eurasian Scientific Herald, 2023)
From this article, information about the life and creative heritage of Abdul Qadir Karomatullah ibn Nematullah Sheikh Sabbaq Bukhari, who lived in the 20th century, was very poorly organized.